Integrating rapamycin with novel PI3K/Akt/mTOR inhibitor microRNAs on NOTCH1-driven T-cell acute lymphoblastic leukemia (T-ALL) - Fateme Arjmand; Samaneh Shojaei; Mitra Khalili; Hossein Dinmohammadi; Behzad Poopak; Samira Mohammadi-Yeganeh; Yousef Mortazavi (BioImpacts)
Introduction: The PI3K/AKT/mTOR signaling pathway plays a significant role in the development of T-cell acute lymphoblastic leukemia (T-ALL). Rapamycin is a potential therapeutic strategy for hematological malignancies due to its ability to suppress mTOR activity. Additionally, microRNAs (miRNAs) have emerged as key regulators in T-ALL pathophysiology and treatment. This study aimed to investigate the combined effects of rapamycin and miRNAs in inhibiting the PI3K/AKT/mTOR pathway in T-ALL cells. Methods: Bioinformatic algorithms were used to find miRNAs that inhibit the PI3K/AKT/mTOR pathway. Twenty-five bone marrow samples were collected from T-ALL patients, alongside five control bone marrow samples from non-leukemia patients. The Jurkat cell line was chosen as a representative model for T-ALL. Gene and miRNA expression levels were assessed using quantitative real-time PCR (qRT-PCR). Two miRNAs exhibiting down-regulation in both clinical samples and Jurkat cells were transfected to the Jurkat cell line to investigate their impact on target gene expression. Furthermore, in order to evaluate the potential of combination therapy involving miRNAs and rapamycin, apoptosis and cell cycle assays were carried out. Results: Six miRNAs (miR-3143, miR-3182, miR-99a/100, miR-155, miR-576-5p, and miR-501- 3p) were predicted as inhibitors of PI3K/AKT/mTOR pathway. The expression analysis of both clinical samples and the Jurkat cell line revealed a simultaneous downregulation of miR-3143 and miR-3182. Transfection investigation demonstrated that the exogenous overexpression of miR- 3143 and miR-3182 can effectively inhibit PI3K/AKT/mTOR signaling in the Jurkat cell line. Moreover, when used as a dual inhibitor along with rapamycin, miR-3143 and miR-3182 significantly increased apoptosis and caused cell cycle arrest in the Jurkat cell line. Conclusion: These preliminary results highlight the potential for improving T-ALL treatment through multi-targeted therapeutic strategies involving rapamycin and miR-3143/miR-3182.